ESTIMATION OF DANGER FROM THE WEST PHILIPPINE TSUNAMI SOURCE TO THE VIETNAMESE COASTAL ZONE - Thuc, Pham Van (Vietnam Journal of Marine Science and Technology, 2007)
The Philippines archipelago is situated between 3 plates: The Philippines Sea Plate in the east, the Sundaland plate in the west and the Indo - Australia in the south. This covergence created a number of trench and subduction zones surrounding the archipelago. The Manila trench and subduction is unique tsunami source can affect to the Vietnamese coastal zones. There were about 8 tsunamis occurred during 300 years such as 1627, 1677, 1744, 1863, 1872, 1924, 1928, 1934 but tsunami with height about 10 m will occur in period of 500 years. The long transmit time (from 2 to 5 hours) from tsunami source to Vietnamese coastal zone will be good condition to reduce human loss if we tsunami warning system in the East Sea.